Chemical composition and pharmacological properties of the essential oils obtained seasonally from Lippia thymoides. (2nd January 2016) - Silva, Fabrício Souza; Menezes, Pedro Modesto Nascimento; Sá, Pedro Guilherme Souza de; Oliveira, André Luís de Santana; Souza, Eric Alencar Araújo; Almeida, Jackson Roberto Guedes da Silva; Lima, Julianeli Tolentino de; Uetanabaro, Ana Paula Trovatti; Silva, Tânia Regina dos Santos; Peralta, Edna Dória; Lucchese, Angélica Maria
Abstract: Context : Lippia thymoides Mart. & Schauer (Verbenaceae) is used in folk medicine to treat wounds, fever, bronchitis, rheumatism, headaches, and weakness. Objective : This study determinates the chemical composition of essential oils from L. thymoides, obtained at during each of the four seasons and correlates with pharmacological properties. Materials and methods : Essential oils were obtained by hydrodistillation and analyzed by gas chromatography coupled to mass spectroscopy (GC-MS). Antioxidant activity was determined by DPPH free radical scavenging and β-carotene bleaching methods. The antimicrobial assays were performed by minimum inhibitory concentration (MIC) and minimum microbicidal concentration (MMC) methods. Isolated rat aorta and uterus, and guinea-pig trachea were utilized to evaluate relaxant potential in pre-contracted smooth muscle. Results and discussion : Essential oils from leaves of L. thymoides had the sesquiterpene β-caryophyllene (17.22–26.27%) as the major constituent followed by borneol (4.45–7.36%), camphor (3.22–8.61%), camphene (2.64–5.66%), and germacrene D (4.72–6.18%). In vitro assays showed that these essential oils do not have antioxidant activity, have antimicrobial selectivity to Gram-positive bacteria Staphylococcus aureus (MIC = 0.004 mg/mL and MMC = 0.26–10.19 mg/mL) and Micrococcus luteus (MIC = 0.03 mg/mL and MMC = 8.43 mg/mL), relax isolated rat aorta (EC50  = 305–544 μg/mL, with endothelium; and EC50  = 150–283 μg/mL, without endothelium), and uterus (EC50  = 74–257 μg/mL), and minor potency, isolated guinea-pig trachea. Conclusions : Lippia thymoides is a source of natural products of pharmaceutical interest, being necessary additional studies to determine the substances involved in the biological activities.